2019
DOI: 10.1017/s0261143019000291
|View full text |Cite
|
Sign up to set email alerts
|

Dougie Young and political resistance in early Aboriginal country music

Abstract: Country music has a reputation for being the music of the American white working-class South and being closely aligned with conservative politics. However, country music has also been played by non-white minorities and has been a vivid way of expressing progressive political views. In the hands of the Indigenous peoples of Australia, country music has often given voice to a form of life-writing that critiques colonial power. The songs of Dougie Young, dating from the late 1950s, provide one of the earliest and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…That is not to say criminology and related fields have not had interest in music and its clear cultural and social relevance in exploring social harms, resistance, redemption and criminalisation. For example Kauzlarich (2012) and Kauzlarich and Awsumb (2017) have highlighted music’s role in protest, resistance and post-colonial policing (also see Martin, 2019); Lee (2010) has explored the role music plays in correctional settings; Hamm (1993) has explored music’s role in recruitment to skinhead Neo-Nazi groups; Ferrell et al (2008) have traced music’s complex association with a range of deviant and resistance cultures, highlighting inter-alia the confusion between rap music and the so-called ‘street gangs’; Linnemann and McClanahan (2017) have similarly explored this slippage in relation to ‘straight edge’ subcultures; Newman (2017) has analysed the pleasures and desires wrapped up in violent or salacious crime story-telling; Muzzatti (2004) has explored the vilification of musicians and scape-goating of music as a cause of violence; Ilan (2020) has used drill music to explore street cultures, where music often highlights the meaning of obscured language, values and rituals; research has also identified how rap lyrics are now often used as evidence in criminal cases featuring musicians, with disproportionately negative outcomes for young black men (Nielson et al, 2019; Rykajdo, 2020). Indeed, there has been a body of scholarship that has focused on hip-hop and gangsta rap, right through to drill music, highly relevant to the current paper 1 .…”
Section: Introductionmentioning
confidence: 99%
“…That is not to say criminology and related fields have not had interest in music and its clear cultural and social relevance in exploring social harms, resistance, redemption and criminalisation. For example Kauzlarich (2012) and Kauzlarich and Awsumb (2017) have highlighted music’s role in protest, resistance and post-colonial policing (also see Martin, 2019); Lee (2010) has explored the role music plays in correctional settings; Hamm (1993) has explored music’s role in recruitment to skinhead Neo-Nazi groups; Ferrell et al (2008) have traced music’s complex association with a range of deviant and resistance cultures, highlighting inter-alia the confusion between rap music and the so-called ‘street gangs’; Linnemann and McClanahan (2017) have similarly explored this slippage in relation to ‘straight edge’ subcultures; Newman (2017) has analysed the pleasures and desires wrapped up in violent or salacious crime story-telling; Muzzatti (2004) has explored the vilification of musicians and scape-goating of music as a cause of violence; Ilan (2020) has used drill music to explore street cultures, where music often highlights the meaning of obscured language, values and rituals; research has also identified how rap lyrics are now often used as evidence in criminal cases featuring musicians, with disproportionately negative outcomes for young black men (Nielson et al, 2019; Rykajdo, 2020). Indeed, there has been a body of scholarship that has focused on hip-hop and gangsta rap, right through to drill music, highly relevant to the current paper 1 .…”
Section: Introductionmentioning
confidence: 99%